2019
DOI: 10.30638/eemj.2019.160
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of Foaming Agent Conditioned Soils Tested on Two Terrestrial Organisms

Abstract: Huge amounts of soil debris are produced during the underground excavation with Earth Pressure Balance-Tunnel Boring Machines (EPB-TBM). Soil debris may contain residual concentrations of the anionic surfactant sodium lauryl ether sulphate (SLES), the main component in some foaming agents used as excavation additives. The reuse of this debris or its discharge as waste is a critical environmental question in construction engineering. There are only few studies on ecotoxicological effects on soil debris coming f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…The overall results of the germination test confirmed the low ecotoxicity of SLES on the considered plants (Lepidium sativum and Zea mays), already highlighted in previous studies (Baderna et al 2015;Grenni et al 2018;Galli et al 2019;Finizio et al 2020). In particular, the germination process, i.e., the reproductive endpoint, appears to be unaffected by SLES, in both species and growth media.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall results of the germination test confirmed the low ecotoxicity of SLES on the considered plants (Lepidium sativum and Zea mays), already highlighted in previous studies (Baderna et al 2015;Grenni et al 2018;Galli et al 2019;Finizio et al 2020). In particular, the germination process, i.e., the reproductive endpoint, appears to be unaffected by SLES, in both species and growth media.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies have tested acute SLES toxicity on model organisms of water and soil communities (Baderna et al 2015;Grenni et al 2018;Galli et al 2019;Finizio et al 2020;Mariani et al 2020), pointing out that, while SLES had severe effects on aquatic organisms, concentration levels usually found in spoil material did not exert toxic effects on soil animals, nor impaired acute ecotoxicological endpoints such as seed germination and root elongation of the tested plant species (Cucumis sativus L., Sorghum saccharatum L., and Lepidium sativum L.). It has been also shown that SLES is easily biodegraded in soils by natural microbial populations, with half-lives ranging from 8 to 46 days, depending on the soil type (Finizio et al 2020;Pescatore et al 2020).…”
mentioning
confidence: 99%
“…Soil debris can be used as a by-product for different purposes, such as refilling old quarries and road construction, raw material for industrial production, filling green areas and in some cases beach nourishment. Although at the FA treatment ratios generally used in tunneling, SLES residues in the spoil material are not toxic for terrestrial organisms, they can be potentially hazardous for aquatic ones because the latter are very sensitive to surfactant residues (Grenni et al, 2018;Galli et al, 2019;Finizio et al, 2020). This means that spoil material can have different concentrations of SLES residues depending on the final destination site (e.g., industrial sites or green areas) and on whether or not there will be a contact with water bodies, (Mininni et al, 2018;Grenni et al, 2019;Finizio et al, 2020;Pescatore et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reports concentrations of SLES in various conditioned soils from excavated tunnels in a range of 27–350 mg/kg soil ( Finizio et al, 2020 ). The presence of SLES can influence spoil material reuse as a by-product if its concentrations are toxic for terrestrial and aquatic organisms ( Grenni et al, 2018 ; Galli et al, 2019 ; Finizio et al, 2020 ). Soil debris can be used as a by-product for different purposes, such as refilling old quarries and road construction, raw material for industrial production, filling green areas and in some cases beach nourishment.…”
Section: Introductionmentioning
confidence: 99%
“…As an effect of contamination, the affected soils can generate a substantial environmental risk for different ecosystems as they are important sources of pollution, which may generate toxicologic effects to ecological receptors and to human health [11][12][13][14]. Chemically degraded soils are characterized by the presence of large amounts of toxic chemicals, and the most common soil pollutants are represented by chlorinated hydrocarbons (CHCs), polycyclic aromatic hydrocarbons (PAHs), phenols, pesticides, mineral oils, cyanides, heavy metals, BTEX (benzene, toluene, ethyl benzene, and xylene), pharmaceutical and personal care products, phthalic acid esters (PAE), radionuclides and others [9,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%